دراسة الأهمية الاقتصادية للزراعة المائية - يعقوب غسان; مياسة وفاء (Latakia University Journal -Biological Sciences Series, 2019)
أجريت الدراسة في منطقة القرير التابعة لمدينة بانياس الساحلية بهدف إبراز الكفاءة الاقتصادية للزراعة المائية، ويقودنا لذلك تفاقم وتدهور أوضاع القطاع الزراعي وارتفاع تكاليف الإنتاج وخاصة الزراعة المحمية التقليدية التي أصبحت في السنوات الأخيرة مصدر قلق لغالبية المزارعين، مما دفع الكثيرين للتفكير بالبحث عن البدائل الأكثر إنتاجية والأقل ضرراً على صحة الإنسان والبيئة، من هذه البدائل وجدنا الزراعة المائية (أي الزراعة بدون تربة Hydroponics). استخدم في الدراسة صالة واسعة تضم عدداً من البيوت البلاستيكية المتصلة ببعضها البعض، أظهرت نتائج الدراسة أن قيمة الربح الصافي من البيت البلاستيكي المزروع بندورة في ظروف الزراعة المائية تقدر بحوالي 208000 ل.س، وأن زمن استعادة رأس المال يساوي سنتين تقريباً، كما أظهرت النتائج أن معامل الربحية بالنسبة لرأس المال المستثمر يقدر بنحو 42%. This study was conducted in the Algarier Area of Banias, which is located on the coast of Syria. The objective of the study was to emphasize the economic efficiency of hydroponic cultures. The driving factors behind carrying out this study were the degradation of agriculture sector situation and the high costs of production, especially traditional protected cultures, which became during the last few years a source of concern to the majority of farmers. These reasons promoted many researchers to look for alternatives that are more productive and less harmful to man and the environment. One of these alternatives is the hydroponic culture (culture without soil). We used in this study a wide hall encompassing several connected green houses. Results showed that the net profit from a hydroponic culture in a green house planted with tomato plants was estimated at 208000 Syrian Pounds. The time period required to recover the invested capital was two years. The study also revealed that the coefficient of profit of the capital invested is about 42%.